Being in the world - Schaflechner, Jürgen (2010)
[Dt.:] Die Website bietet Filmmaterial zu Pakistans kultureller Vielfalt, zu religiösen, künstlerischen und historischen Aspekten der Hindu-Bevölkerung in der Islamischen Republik. - [Engl.:] This site's intention is to introduce, through a differentiated perspective, Pakistan's cultural plurality. Primarily it seeks to offer some first insights in religious, artistic and historic elements of Hindu life in the Islamic Republic.